Biostatistics : a foundation for analysis in the health sciences - Daniel, Wayne W., 1929-; Cross, Chad Lee, 1971- (Hoboken, NJ : Wiley, 2019)
"The ability to analyze and interpret enormous amounts of data has become a prerequisite for success in allied healthcare and the health sciences. Now in its 11th edition, Biostatistics: A Foundation for Analysis in the Health Sciences continues to offer in-depth guidance toward biostatistical concepts, techniques, and practical applications in the modern healthcare setting. Comprehensive in scope yet detailed in coverage, this text helps students understand--and appropriately use--probability distributions, sampling distributions, estimation, hypothesis testing, variance analysis, regression, correlation analysis, and other statistical tools fundamental to the science and practice of medicine. Clearly-defined pedagogical tools help students stay up-to-date on new material, and an emphasis on statistical software allows faster, more accurate calculation while putting the focus on the underlying concepts rather than the math. Students develop highly relevant skills in inferential and differential statistical techniques, equipping them with the ability to organize, summarize, and interpret large bodies of data. Suitable for both graduate and advanced undergraduate coursework, this text retains the rigor required for use as a professional reference." --
Introduction to biostatistics -- Descriptive statistics -- Some basic probability concepts -- Probability distributions -- Some important sampling distributions -- Estimation -- Hypothesis testing -- Analysis of variance -- Simple linear regression and correlation -- Multiple regression and correlation -- Regression analysis : some additional techniques -- The chi-square distribution and the analysis of frequencies -- Nonparametric and distribution-free statistics -- Survival analysis -- Vital statistics
Includes bibliographical references and index
Keywords: Medical statistics; Biometry; Biostatistics; Biometry